1989
DOI: 10.1042/bj2610483
|View full text |Cite
|
Sign up to set email alerts
|

Purification of bovine brain inositol 1,4,5-trisphosphate 3-kinase. Identification of the enzyme by sodium dodecyl sulphate/polyacrylamide-gel electrophoresis

Abstract: Inositol 1,4,5-trisphosphate (InsP3) 3-kinase catalyses the ATP-dependent phosphorylation of InsP3 to inositol 1,3,4,5-tetrakisphosphate (InsP4). A method is presented for the rapid purification of InsP3 3-kinase from bovine brain by calmodulin (CaM)-Sepharose affinity chromatography. Maximal activation of the purified InsP3 3-kinase by Ca2+/CaM was 6-7-fold as compared with the activity measured in the presence of EGTA (1 mM) and 10 microM-InsP3. At 10 microM-InsP3 and 0.1 mM free Ca2+, half-maximal activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…Based on purification of the bovine and rat brain enzyme, IP3kinA activity and protein have been described as cytosolic (17)(18)(19), in contrast to type I 5-phosphatase that appears to be mostly membrane-bound (20). Immunocytochemical studies employing antibodies against the purified rat brain enzyme revealed IP3kinA to be very concentrated on membranes and throughout the cytosolic matrix of dendritic spines (7,8).…”
Section: Inositol 145-trisphosphate (Ip 3 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on purification of the bovine and rat brain enzyme, IP3kinA activity and protein have been described as cytosolic (17)(18)(19), in contrast to type I 5-phosphatase that appears to be mostly membrane-bound (20). Immunocytochemical studies employing antibodies against the purified rat brain enzyme revealed IP3kinA to be very concentrated on membranes and throughout the cytosolic matrix of dendritic spines (7,8).…”
Section: Inositol 145-trisphosphate (Ip 3 )mentioning
confidence: 99%
“…The B isoform of IP3kin, which is expressed in most cells and in glia in brain (5, 15), is localized to internal membranes of the endoplasmic reticulum and Golgi apparatus, where it is poised to regulate IP 3 concentrations near calcium stores (16). In contrast, nothing is known about targeting mechanisms for isoform A in neurons.Based on purification of the bovine and rat brain enzyme, IP3kinA activity and protein have been described as cytosolic (17)(18)(19), in contrast to type I 5-phosphatase that appears to be mostly membrane-bound (20). Immunocytochemical studies employing antibodies against the purified rat brain enzyme revealed IP3kinA to be very concentrated on membranes and throughout the cytosolic matrix of dendritic spines (7,8).…”
mentioning
confidence: 99%
“…By contrast, the Km for ATP was found to be 2.1 + 0.47 mM, suggesting that the enzyme might not be fully saturated with ATP under conditions that prevail in the cell. Alternatively, the enzyme's affinity for Ins(1,4,5)P, 3-kinase that is stimulated by Ca2+/calmodulin (Li et al, 1989;Takazawa et al, 1989;Shears, 1989 (Downes et al, 1982;Irvine et al, 1986;Shears, 1989). The relative activities of these two pathways for Ins(1,4,5)P3 metabolism vary between cells and according to the stimulatory conditions.…”
Section: Western Blottingmentioning
confidence: 99%
“…Ins(l,4,5)P3-3-kinase activity is also localised primarily in the cytosolic fractions of bovine brain [54] and rat liver [551 and guinea pig peritoneal macrophages [56]. The apparent K, (0.42 pM) of the purified muscle Ins(1,4,5)P3 3-kinase for Ins (1,4,5)P3 is similar to that reported in other tissues (0.21-0.70 pM) [54,[57][58][59][60].…”
Section: Kinetics Of Ins( 145)p3 and Ins(1345)p4 Metabolismmentioning
confidence: 96%
“…Ins(l,4,5)P3-3-kinase activity is also localised primarily in the cytosolic fractions of bovine brain [54] and rat liver [551 and guinea pig peritoneal macrophages [56]. The apparent K, (0.42 pM) of the purified muscle Ins(1,4,5)P3 3-kinase for Ins (1,4,5)P3 is similar to that reported in other tissues (0.21-0.70 pM) [54,[57][58][59][60]. The conversion of Ins( 1,4,5)P, to Ins( 1 ,3,4,5)P4 may be a secondary pathway for Ins(1,4,5)P3 metabolism, with the main function of Ins( 1,4,5)P, 3-kinase being to regulate the relationship between 1ns(1,4,5)P3 and Ins(1,3,4,5)P4, whose roles in Ca2+ signalling may be closely associated [61].…”
Section: Kinetics Of Ins( 145)p3 and Ins(1345)p4 Metabolismmentioning
confidence: 96%